2022
DOI: 10.1177/1759720x221137125
|View full text |Cite
|
Sign up to set email alerts
|

Higher body mass index is associated with a lower iloprost infusion rate tolerance and higher iloprost-related adverse events in patients with systemic sclerosis

Abstract: Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by vasospasm and microvascular involvement. Iloprost (ILO), a prostaglandin analogous, is used for the treatment of SSc-related Raynaud’s phenomenon and digital ulcers. The suggested dose is 0.5–2 ng/kg/min for 6–8 h, and the maximum dose is decided upon the patient’s tolerance. Objectives: This study aims to analyze ILO infusion tolerance and possible predictive factors in patients with SSc. Design: This is a retrospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Hypotension, headaches and flushing comprise some of their most encountered side effects and are mainly associated with the intravenous route of administration; however, a dose tapering to 0.5 ng/kg/min leads to a resolution of most adverse events in the majority of cases [ 4 , 5 ]. BMI seems to be a major predictive factor of drug intolerance, as overweight patients tolerate lower iloprost infusion rates and have a 13-fold increased risk of developing adverse effects [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypotension, headaches and flushing comprise some of their most encountered side effects and are mainly associated with the intravenous route of administration; however, a dose tapering to 0.5 ng/kg/min leads to a resolution of most adverse events in the majority of cases [ 4 , 5 ]. BMI seems to be a major predictive factor of drug intolerance, as overweight patients tolerate lower iloprost infusion rates and have a 13-fold increased risk of developing adverse effects [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…They also cease shortly after the infusion is discontinued. A recent study in patients with systemic sclerosis observed that overweight and obese patients were more susceptible to iloprost adverse effects [ 25 ].…”
Section: Introductionmentioning
confidence: 99%